A novel assisted reduction method in extra-articular fractures of the distal tibia treated with intramedullary nail - Liu, Jun; Dai, Simin; Liu, Lijin; Kuang, Hailin; Yan, Liang; Cai, Qiangqiang; Shao, Zongzuan; Wei, Wenbo; Min, Zhihai; Tang, Wubing (Frontiers in Medicine, 2024)
Background: To explore the clinical efficacy and safety of Kirschner wires (KWs) as a blocking screw technique for extra-articular fractures of the distal tibia treated with intramedullary nails (IMNs).Methods: Fifty-three patients were treated with KW-assisted IMN for extra-articular fractures of the distal tibia via the blocking screw technique or poller screw (PS) technique. The operation time, number of fluoroscopies, number of blocking screws used, blood loss and time to union were compared between the two groups. Additionally, the functional outcomes of the two groups were compared using range of motion (ROM), visual analog scale (VAS), American Orthopedic Foot and Ankle Society (AOFAS), and Lysholm scores.Results: Compared with those in the PS group, the operation time in the KW group was significantly shorter, and the number of fluoroscopy procedures and amount of blood loss during KW surgery were also significantly lower (P = 0.014, 0.001, and 0.036, respectively). Regarding the functional outcomes, there were no significant differences in the ROM, VAS score, AOFAS score or Lysholm score between the two groups (P > 0.05).In the treatment of extra-articular fractures of the distal tibia with nails, the use of KW as a blocking screw technique is safe and reliable.